"Dad, Wash Your Hands": Gender, Care Work, and Attitudes toward Risk during the COVID-19 Pandemic. (October 2020) - Umamaheswar, Janani; Tan, Catherine
Recent analyses of responses to coronavirus disease 2019 (COVID-19) have posited that men's dismissive attitudes toward the risks of the virus reflect their attempts to conform to masculine norms that valorize bravery and strength. In this article, the authors develop an alternative account of the gender differences in attitudes toward COVID-19. Drawing on three waves of in-depth interviews with college students and members of their households ( n = 45) over a period of 16 weeks (for a total of 120 interviews), the authors find that men and women in comparable circumstances perceive similar risks of COVID-19, but they diverge in their attitudes toward, and responses to, these risks. Connecting scholarship on gender and care work with research on risk, the authors argue that gender differences in attitudes toward risk are influenced by the unique and strenuous care work responsibilities generated by the COVID-19 pandemic, which are borne primarily by women—and from which men are exempt.